2008 42nd Annual IEEE International Carnahan Conference on Security Technology 2008
DOI: 10.1109/ccst.2008.4751292
|View full text |Cite
|
Sign up to set email alerts
|

Securing a Health Information System with a government issued digital identification card

Abstract: Health Information Systems (HIS) are often deployed with inadequate security solutions. Given the importance and sensitivity of this matter and to guarantee the rule of law, as well as the legal and ethical value of decisions made in a hospital setting, often dealing with life/death situations, there is an urgent need for a much better provisioning of health information systems security.The launch of the Portuguese digital national identification smart card, the Citizen Card (CC), with strong authentication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Our results corroborate and add to the findings in the literature review carried out by Santos et al (2008). As noted in Section 2, Santos et al (2008) found that health-care professionals' use of eID cards raises such challenges as usability, resistance to use, inefficiency and the risk of leaving the card at home. As illustrated in this paper, we found the very same issues in our empirical material.…”
Section: Contribution To Researchsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results corroborate and add to the findings in the literature review carried out by Santos et al (2008). As noted in Section 2, Santos et al (2008) found that health-care professionals' use of eID cards raises such challenges as usability, resistance to use, inefficiency and the risk of leaving the card at home. As illustrated in this paper, we found the very same issues in our empirical material.…”
Section: Contribution To Researchsupporting
confidence: 89%
“…As noted in Section 2, Santos et al (2009) found that health care professionals' use of eID cards raises such challenges as usability, resistance to use, inefficiency, and the risk of leaving the card at home. As illustrated in this paper, we found the very same issues in our empirical material.…”
Section: Contribution To Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of countries were on a cross roads either to accept fear of terrorism or privacy (Matar, 2003), in Portugal the government linked access to health services with national ID (Santos, Correia, & Antunes, 2008), globally the national ID was meant for security reasons (Bennett & Lyon, 2013), in Asia especially Malaysia the citizens were querying the security issues on the national ID (Kee, Nee, Beng, & Fun, 2012) Shukri questioned the privacy and security of the national IDs (Kuada, Wiafe, Addo, & Djaba, 2017;Shukri & Hafiz, 2015), they system doesn't allow negotiations with another person in terms of cross checking identity and were irregularities are found its invalid national ID (Haala, 2005(Haala, , 2008, the National ID projects around the world are demeaning identity (Sobel, 2001), the national ID system has been reduced to who belongs to United States (Redman, 2008) and in Canada the national ID was resisted with reasons (Marleau, 2003). From the above analysis its clear that countries faced a lot of resistance to introduce the national IDs.…”
Section: Literature Reviewmentioning
confidence: 99%